VD_FINDINFO Jug / 2010 / 71 vom 12. Mai 2010 - VD Tribunal cantonal (2010)
SURVENANCE DU CAS D'ASSURANCE, DEMANDE DE PRESTATION D'ASSURANCE, PERPETUATIO FORI, PRESTATION CARACTÉRISTIQUE, INTÉRÊT MORATOIRE, LÉGALISATION | 104 al. 1 CO, 38 LCA, 41 al. 1 LCA, 97 al. 1 LCA, 98 al. 1 LCA, 117 al. 2 LDIP, 117 al. 3 LDIP, 5 LDIP, 9 al. 2 LDIP